An innovative method for placing a double-lumen irrigation-suction tube in the management of abdominal infection: A case report. Issue 9 (March 2018) - Yao, Zheng; Tian, Weiliang; Xu, Xin; Huang, Qian; Zhao, Yunzhao
Abstract: Rationale: Currently, the use of double-lumen irrigation-suction tube for drainage has become increasingly more common. However, the insertion process is complex, and the position of the double cannula placed in this manner is not accurate. We developed a method for placing the drainage tube and use it in the treatment of an abdominal infection. Patient concerns: A 51-year-old man with an abdominal infection due to colonic anastomotic fistula was admitted. Routine laboratory tests revealed an elevated white blood cell count (17 × 10 9 /L) and C-reactive protein level (78 mg/L). Computed tomography (CT) revealed that the peritoneal cavity was filled with fluid. Diagnoses: The patient was diagnosed with colonic anastomosis fistula by gastrointestinal radiography. Abdominal infection was diagnosed based on CT scan, inflammatory markers, and patient signs and symptoms. Interventions: Two punctures were performed. After skin expansion, the source of infection was drained with a suction catheter (diameter = 1.0 cm) under continuous negative pressure of 150 to 200 millibars, along with continuous saline irrigation at 300 mL/h. Outcomes: Pus in the abdomen drained completely. The abdominal infection was controlled. There were no adverse events. Lessons: Abdominal infection in fistulas is a fatal disease. The main therapeutic target is full drainage at an early stage. Precise positioning of the tube, continuous negative pressure irrigation and drainage are key points in the treatment.